KEPEMIMPINAN INOVATIF DALAM UPAYA MENINGKATKAN PELAYANAN PUBLIKDI KECAMATAN KOTA SUMENEP - Ghufrony, Ahmad; Kadarisman, Kadarisman (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Inovatif behaviour is often related to creativities. Both of it is true, butbehavioral construct of creativity and inovatif have various difference. Its impactalmost at all of life area, do not aside from governance sector and also of publicorganisation applied by a leader specially District of Town of Sumenep. Focus ofthis research which will reach that is " to know leader of inovatif in the effortimproving service of public in Kecamatan Kota Sub-Province of Sumenep". Datawich used is primary data and of sekunder. Research subyek that is using keyinforman. Was gathered, hence technique analyse data conducted step by step:data reduction, presentation of phase and data of take a summary later;then alsodone authenticity of data. Conclusion of this research oriented its intention dutyof consistency of style or leader attitude of inovatif to improve service of public,relation orienting that is owning ability manage or construct officer in officedistrict of town in finishing work and also oriented change that meant by repair ofstrategic decision to environmental behavior, making change specially processarea, product, service, and its comitment.